From Ansel Adams to Andy Warhol : Portraits and Self-Portraits from the University of Michigan Museum of Art - Hennessey, William; Smith, Graham; Gabinetto Disegni e Stampe degli Uffizi, Florence; The University of Michigan Museum of Art, Ann Arbor (Ann Arbor : The Regents of the University of Michigan, 1994)
Adamson, John ; Avedon, Richard ; Beal, Jack ; Beckmann, Max ; Bohnen, Blythe ; Boilly, Julien-Léopold ; Brassaï ; Bullock, Wynn ; Campendonk, Heinrich ; Close, Chuck ; etc.
From Ansel Adams to Andy Warhol, Gabinetto Disegni e Stampe degli Uffizi, Florence, 1 February - 27 March 1994 / The University of Michigan Museum of Art, Ann Arbor, 11 June - 14 August 1994
boek
Keywords: Warhol, Andy; Adams, Ansel